Volatility spillover and dynamic co-movement of foreign direct investment between Malaysia and China and developed countries - Mori Kogid; Jaratin Lily; Rozilee Asid; James M. Alin; Dullah Mulok (Springer Nature Switzerland AG., 2022)
This study delves into the relationship between Malaysia and several countries—China, Singapore, Japan and the United States of America (USA), through FDI relations using the multivariate GARCH model. The annual time series data was used over the period of 1982 to 2017. The study was able to prove statistically, of a significant volatility spillover between Malaysia and China, Singapore, Japan and the USA. The study also found that the relationship between FDI for all these countries varied over time, which was dynamic in nature. Relatively low (weak) correlations occurred between Malaysia and Singapore and Japan, while high (strong) correlations occurred between Malaysia and China and the USA. In addition, the finding also showed that although there was evidence due to significant impacts, both the Asian financial crisis and the global financial crisis did not entirely affect the market trends and the relationship between foreign direct investments across all these countries.